OPTIMALISASI PENGGUNAAN FAKTOR PRODUKSI PADA USAHA TANI KAKAO DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Nurchaini, Dewi Sri; Damayanti, Yusma; Ulma, Riri Oktari (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
This research was conducted in KumpehSubdistrict, Muaro Jambi District, with respondents being cocoa farmers. This research was conducted with the aim of : 1. To know the description of the production function of cocoa farming 2. Analyzing the level of optimization / economic efficiency of the use of production factors in cocoa farming, and 3. Performing a calculation approach to determine the optimal use of production factors on cocoa farming. Farmers who were chosen as respondents were selected purposively, namely farmers who have cocoa at an optimal age of 9-14 years. The number of farmers who met these criteria was 55 people and the technique of taking respodentswas carried out by census. The analytical method used is the Cobb Douglas production function analysis, then the optimization calculation is continued with economic efficiency criteria, where the efficiency of the use of production factors is achieved if NPMXi / HXi = 1. From the results of the analysis and discussion it can be concluded that: 1) The use of land production factors and technical / physical labor influences the increase in cocoa production / hectare / year, while fertilizers and medicines have no effect on production. 2) The use of factors of production of labor, fertilizers and medicines in cocoa farming is not yet economically efficient. 3) From the results of optimization, the use of work can be increased up to 238.5 HOK / hectare / year or increased by 167.64 HOK from the actual workforce poured out by farmers. While the use of fertilizer (X2) can be added up to 2,293.28 kg / year / hectare or added 1,340.38 kg of actual use and medicines (X3) added to 9.50 liters or added 0.87 liters of the amount of drugs medicine used by farmers.